2020
DOI: 10.1002/cphc.202000199
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Metastable Inorganic Solids with Extended Structures

Abstract: The number of known inorganic compounds is dramatically less than predicted due to synthetic challenges, which often constrains products to only the thermodynamically most stable compounds. Consequently, a mechanism‐based approach to inorganic solids with designed structures is the holy grail of solid state synthesis. This article discusses a number of synthetic approaches using the concept of an energy landscape, which describes the complex relationship between the energy of different atomic configurations as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 118 publications
4
65
0
Order By: Relevance
“…By decomposing the overall phase evolution into a sequence of pairwise reactions, we can calculate the thermodynamics and analyze the kinetics of each reaction step separately, providing a simplified theoretical picture to conceptualize and navigate ceramic synthesis. [ 15,17–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…By decomposing the overall phase evolution into a sequence of pairwise reactions, we can calculate the thermodynamics and analyze the kinetics of each reaction step separately, providing a simplified theoretical picture to conceptualize and navigate ceramic synthesis. [ 15,17–20 ]…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been shown that the elements in the ultrathin layer can diffuse into the bulk material at the interface, before nucleation of the most thermodynamically stable phase. 64 Hence, it is possible that what we nd here, as Co-diffusion into LLTO and loss of LCO in the absence of any other secondary phases, is due to such a metastable path, instead of formation of the phases that were predicted by DFT to be thermodynamically stable. It is also possible that, even if such secondary phases formed, they were in too small amounts or not well crystallized, that we could not detect them with XRD up to 600 C. Our results from XRD are in agreement with the observed stability of the LCOjLLTO mixed powders by Liao et al, who also did not observe secondary phase formation till 700 C. 48 Importantly, our ndings in this work show that the LCOjLLTO system undergoes signicant interaction, especially in the form of elemental mixing (of Co in particular) upon thermal treatment, even if no secondary phases were detectable by XRD or XAS up to 700 C.…”
Section: Discussionmentioning
confidence: 82%
“…In situ characterization techniques offer many opportunities in solid‐state research, such as exploration of crystal structure and properties at non‐ambient conditions [22–24] . Especially time‐resolved studies of chemical reactions involving solids are very beneficial; they unveil reaction pathways and add dynamics to the otherwise often static picture of solid‐state reactions [25,26] . Sapphire single‐crystal based gas‐pressure cells allow for time‐resolved in situ neutron powder diffraction studies under hydrogen (deuterium) gas pressure and elevated temperature.…”
Section: Introductionmentioning
confidence: 99%